Trusted Systems 5th International Conference, INTRUST 2013, Graz, Austria, December 4-5, 2013, Proceedings - Bloem, Roderick; Lipp, Peter; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
This book constitutes the thoroughly refereed conference proceedings of the 5th International Conference on Trusted Systems, INTRUST 2013, held in Graz, Austria, in December 2013. The revised full papers focus on the theory, technologies and applications of trusted systems. They cover all aspects of trusted computing systems, including trusted modules, platforms, networks, services and applications, from their fundamental features and functionalities to design principles, architecture and implementation technologies.
Hardware-Based Security and Applications -- Para-Virtualizing the Trusted Platform Module: An Enterprise -- Framework Based on Version 2.0 Specification -- The PACE|CA Protocol for Machine Readable Travel Documents -- A Spatial Majority Voting Technique to Reduce Error Rate of Physically Unclonable Functions -- Access Control, Integrity and Policy Enforcement.
Keywords: Computer science; Operating systems (Computers).; Data protection; Data encryption (Computer science).; Computer Science; Systems and Data Security; Data Encryption; Operating Systems